ANALISIS PENYELENGGARAAN PENGAWASAN PROGRAM PENDAMPINGAN IBU HAMIL DAN IBU NIFAS RISIKO TINGGI OLEH TIM PENGGERAK PKK KECAMATAN PEDURUNGAN (DALAM PERSPEKTIF PERENCANAAN DAN MEKANISME) - Matsna Haniifah; Sutopo Patria Jati; Rani Tyas Budiyanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Maternal Mortality Rate in Pedurungan Sub-District is highest number in Semarang 2018. PKK movement has an important role to empower community in handling maternal mortality rates through assistance program for pregnant women and postpartum mothers high risks. However this program target not achieved due to lack of supervision of program implementation. This study aims to analyze execution of supervision in this program by PKK activator team in Pedurungan sub district from mechanism flow and planning perspective. Qualitative research with descriptive analytic approach by indepth interview method with purposive sampling. Subject is head and head of Pokja 4 PKK Activator Team Pedurungan Regency as main informants. Triangulation informants were head and head of Pokja 4 PKK Activator Team Pedurungan Tengah Village and head of Pokja 4 PKK Activator Team Semarang. Results show that mechanism flow of PKK Movement not clearly imaged tasks and function, incomplete planning process in determining time of supervision, setting focus of supervision was not in accordance with cause of problem, human resource planning not enforced, funding planning not implemented . Advised to repair PKK Movement mechanism flow and enforced supervision planning guided by Government Regulation Number 12 of 2017 and the results of RAKERNAS VIII PKK 2015